PERBANDINGAN METODE ALGORITMA C4.5 DAN NAÏVE BAYES UNTUK MEMPREDIKSI KELULUSAN MAHASISWA - Aulia Rahmayanti; Lili Rusdiana; Suratno Suratno (Walisongo Journal of Information Technology, 2022)
This study was conducted to compare the accuracy of two algorithm methods, namely the C4.5 algorithm and Naïve Bayes algorithm on a number of datasets. The sources of datasets used are student data of the Informatics Engineering Study Program (STMIK Palangkaraya) where each dataset has a different amount of data (instances) and number of attributes. Based on the results of the comparison study of the C4.5 and Naïve Bayes Algorithm for Predicting the On-time Graduation of STMIK Palangkaraya Students, the results obtained from the accuracy of the two algorithms show that the accuracy of the C4.5 Algorithm is 90% better than the Naïve Bayes algorithm, which is only 85%.  The C4.5 algorithm also gives values on recall and precision of 92% and 94% better than the Naïve Bayes algorithm with values of 86% and 93%, respectively.